Active partnership, community engagement, and intersectoral collaboration are needed to enhance the successful implementation of inclusive education at full-service schools - Mokwena Morelle; Glory Maria Morelle (International Journal of Studies in Inclusive Education)
This study outlines the aftermaths of active participation, community engagement, and intersectoral collaboration in enhancing the successful implementation of inclusive education at full-service schools. It also discusses the maximum support schools need to cater to the needs of learners with learning barriers. It employed a qualitative approach, where teachers from full-service schools were interviewed. Senior Education Specialists were also engaged in the study as they are the cornerstones in enhancing the successful implementation of inclusive education in full-service schools. Data were analysed by content analysis. This study found active partnership, community engagement, and intersectoral collaboration as factors that could enhance the successful implementation of inclusive education in full-service schools.